Utilization of eco-tourism in Bangli regency of Penglipuran village as a bamboo forest conservation center in Bali - I Wayan Muliawan; Ni Made Widya Pratiwi (Master Program of Infrastructure and Environmental Engineering, Postgraduate Program, Warmadewa University, 2023)
Penglipuran Village is one of the icons of tourism in Bali which is located in Kubu District, Bangli Regency. Penglipuran Village has its own uniqueness and charm, one of which is the existence of a bamboo forest that protects the village. This bamboo forest has an area of ​​up to 45 hectares that surrounds this village and continues to be maintained and preserved. The people of Penglipuran Village believe that the bamboo forest has a function as a water catchment area, so this forest is called a village protection forest. This study focuses on the use of ecotourism in Penglipuran Village, Bangli Regency as a center for bamboo forest conservation in Bali, which can create a balanced community economic growth between humans and nature. The method used in this study, namely quantitatively by conducting interviews with Penglipuran Village owners related to bamboo forest management, then analyzed using SWOT to determine the strategy for using ecotourism in Penglipuran Village, Bangli Regency as a Bamboo Forest Preservation Center in Bali. From the results, it was found that the strength in the use of ecotourism in Penglipuran Village is the existence of community support for the preservation of bamboo forests, with a weakness that is limited sources of funds for development. Opportunities from the use of ecotourism are that the need for tourist objects is increasing, with the threat of forest degradation threatening sustainability.